Comparative study of accident-tolerant fuel for a CANDU lattice - Younan, Simon (My University, 2017)
Since the Fukushima accident in 2011, there have been an increasing number of studies on the use of accident-tolerant fuel (ATF) in light water reactors to mitigate the consequences of a future severe accident, by better retaining fission products and/or providing operators more time to implement emergency measures. However, few studies exist for CANDU reactors in this regard. The goal of this study is to determine how different types of ATF are expected to behave in a CANDU lattice when compared to the current UO2 fuels. In particular, this study focuses on neutronic parameters calculated using the Serpent 2 code, but also models heat transfer and stylized accident scenarios. The ATF concepts tested include UO2-SiC composites, UN and UN-based composites, U-9Mo, and fully ceramic microencapsulated (FCM) fuel, along with SiC and SS-coated cladding. Four general conclusions can be drawn: 1. Fuel temperature are lower for ATF as compared to traditional fuels. UO2-SiC composite fuel exhibits a moderate temperature reduction compared to UO2, particularly for fresh fuel. Other ATF fuel materials exhibit a substantial decrease in fuel temperature compared to UO2. The lower fuel temperatures are also accompanied by lower melting temperatures for some fuels, hence each design requires specific assessments on safety. 2. As most ATF have a poorer neutron economy compared to standard fuel designs, enrichment is required to use ATF in a CANDU, particularly for UN and FCM fuel compositions. Coolant void reactivity (CVR) is lowest with FCM fuel and highest with U-9Mo fuel. Fuel temperature coefficient (FTC) is most negative for fuel containing UN or U-9Mo. 3. Changing the cladding material from zircaloy to SiC slightly improves neutron economy, while a FeCrAl surface layer impairs neutron economy. The impact of many ATF sheath materials is to greatly reduce or eliminate hydrogen production in some severe accidents. A specific assessment on hydrogen production was not performed in this study. 4. In stylized accident scenarios, all fuels exhibit only a small temperature spike due to the reactivity insertion of the LOCA as the reactor shutdown limits the power excursion. For cases where Emergency Core Cooling functions as designed, fuel and channel failures are precluded for both traditional fuels and ATF. For cases with impairment of ECC, most ATF fuels show lower fuel temperatures than UO2 fuels and adequate heat removal to the pressure-calandria tube fuel channel. The exception would be Mo-based fuels that reach the melting point prior to establishing an adequately high sheath temperature to sustain radiative heat removal to the PT-CT assembly.
Comparative study of ATF for a CANDU lattice
McMaster University MASTER OF APPLIED SCIENCES (2017) Hamilton, Ontario (Engineering Physics) TITLE: Comparative study of accident-tolerant fuel for a CANDU lattice AUTHOR: Simon Younan, B.Eng. (McMaster University) SUPERVISOR: Dr. David Novog NUMBER OF PAGES: xiii, 120
Keywords: nuclear engineering; reactor physics; CANDU; accident-tolerant fuel; Serpent 2; Monte Carlo; accident-tolerant cladding